Comparision between coelomocyte cells isolated from coelomic cavity of earth worm and leucocytes - Mohammad, Saba T. (University of Thi-Qar Journal of Science, 2014)
The coelomocytes of Lumbricus terrestris have been isolated &described by used simple &modified method, ,theviability of isolated cells were (85%), and to diffrentiate the type of cells, stained by Leishmans stain,have beenobserved the more type cells which (granulocyte&neutrophile).All cell types, produce pseudopodia and are capable of phagocytosis. The phagocytotic activity of the coelomocytes to engulf. Killed yeast cells (Saccharomyces cerevisiae) assessed in vitro and compared with phagocytic cells(polymorphic nuclear cell) isolated from human, was found the phagocytosis process increase with time the capacity of human phagocyte to excel in phagocytosis compared with coelomocyte was (86.1% , 67.1% ) respectively.